Frameworks for ICT policy : government, social and legal issues 2026-02-15T20:58:52+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Adomi, Esharenana E. (Information Science Reference, 2011)

(untitled)
"This book provides policy-relevant insights and information to aid those engaged in systematic research and teaching about ICT policy formation and implementation"--Provided by publisher